Composing differences: imagining new models for knowledge production and exchange - Bobin, Virginie (New York Les presses du réel, 2015)
Comprising a montage of theoretical and speculative texts, conversations, fictions, and documents, this volume explores different tactics of production and intellectual exchange that operate in the interstices between artistic, educational, and political contexts. In so doing, it imagines novel institutional forms at a time when a rhetorical crisis dominates the economic world, and when politics and media are pretexts for a growing privatisation of knowledge. Editor and writer Virginie Bobin thereby presents possible practices for the invention dynamic commons, based on the programme of research and events organised in the context of the ART2 festival (April 2014, New York).